Inversion domain boundaries in Mn and Al dual‐doped ZnO: Atomic structure and electronic properties. Issue 9 (22nd May 2017) - Hoemke, Joshua; Tochigi, Eita; Tohei, Tetsuya; Yoshida, Hidehiro; Shibata, Naoya; Ikuhara, Yuichi; Sakka, Yoshio
Abstract: The atomic and electronic structures of inversion domain boundaries in Mn‐Al dual‐doped ZnO (Zn0.89 Mn0.1 Al0.01 O) have been investigated. Using atomic‐resolution scanning transmission electron microscopy, a head‐to‐head c ‐axis configuration and cation stacking sequence of αβαβ|γ|αβαβ along the c ‐axis were observed at the basal‐plane inversion domain boundary. Energy‐dispersive X‐ray spectroscopy and electron energy‐loss spectroscopy revealed significant localization of Mn and minor localization of Al at the basal‐plane inversion domain boundary. Based on experimental findings, a Mn‐doped basal‐plane inversion domain boundary slab model was constructed and refined by first principles calculations. The model is in agreement with atomic‐resolution images. The local electronic density of states of the slab model basal‐plane inversion domain boundary shows a hybridization of the Mn d and O p states within the valence band and localized Mn d states in the conduction band. The thermoelectric properties of Zn0.99− x Mn x Al0.01 O ceramics have been reported in a previous work. In this work, the effects of inversion domain boundaries on the thermoelectric properties are discussed. In comparison to Zn0.99− x Mn x Al0.01 O ceramics with x ≤0.05, inversion domain boundaries in Zn0.89 Mn0.1 Al0.01 O caused thermal and electrical conductivity reduction due to interface scattering of phonons and electrons. The Seebeck coefficient increased, suggesting electron filtering at inversion domain boundaries.